Bonding, Bridging, and Becoming a Teacher: Student Cohorts and Teacher Identity - Hasinoff, Shelley; Mandzuk, David (Alberta Journal of Educational Research, 2005)
This research examines the effects of social capital on teacher identity in a sample of undergraduate after-degree education students who took most or all of their courses together as a cohort. A theoretical model containing nine variables including university and social background, social capital, and teacher identity is presented. The data obtained from questionnaires completed by 239 students in the Faculty of Education at a Western Canadian university are used to test the model. The results indicate that when other variables are taken into account, students’ perceptions of social capital resources available in their cohort have direct and indirect effects on their teacher identity.